The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12966-021-01221-9
|View full text |Cite
|
Sign up to set email alerts
|

Behaviours that prompt primary school teachers to adopt and implement physically active learning: a meta synthesis of qualitative evidence

Abstract: Background Physically active learning (PAL) - integration of movement within delivery of academic content - is a core component of many whole-of-school physical activity approaches. Yet, PAL intervention methods and strategies vary and frequently are not sustained beyond formal programmes. To improve PAL training, a more comprehensive understanding of the behavioural and psychological processes that influence teachers’ adoption and implementation of PAL is required. To address this, we conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 75 publications
4
19
0
Order By: Relevance
“…This study indicates that successful implementation of PASD requires complex interactions and engagement across the whole school system, which corresponds with recent findings on the successful implementation of PAL (33,34), a key part of PASD. A total of 36 decisive factors for the successful implementation of PASD in Danish schools were identified using a group Delphi process, which included 57 stakeholders from all parts of the school system.…”
Section: Discussionsupporting
confidence: 90%
“…This study indicates that successful implementation of PASD requires complex interactions and engagement across the whole school system, which corresponds with recent findings on the successful implementation of PAL (33,34), a key part of PASD. A total of 36 decisive factors for the successful implementation of PASD in Danish schools were identified using a group Delphi process, which included 57 stakeholders from all parts of the school system.…”
Section: Discussionsupporting
confidence: 90%
“…Another interesting aspect of that study was that, even without implementing it, many headteachers perceived PAL as compatible with the national curriculum (36). Implementing a new learning strategy is challenging and could be even more so depending on a teacher’s commitment to and perception of its delivery (17).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, active leadership was emphasized as one of the most important factors for the implementation of PA (52). This is supported by the synthesis by Daly-Smith et al (15), which found that it is imperative to engage all levels of the school community for successful implementation of PAL, including leadership. The involvement of the principal might also depend on the principal's own attitude toward and experience of PA.…”
Section: Implementation Strategiesmentioning
confidence: 94%
“…In ACTIVE SCHOOL, the interplay between skills learned through courses, materials, and tools used in the preparation of lessons and the opportunities to discuss and share practices at team meetings are all elements assumed to promote ongoing intervention delivery. This can lead to personalized and professional adaptations of the intervention, and working with pupils and collaborating with colleagues over time can develop this further (15,51). In a 1-yr, school-based PA intervention, adaptations were investigated in a group of the intervention schools that were rated with the best overall implementation (49).…”
Section: Implementation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation